2009
DOI: 10.1080/09709274.2009.11906152
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Level of Fertilizer Utilization for Cocoa Production in Nigeria

Abstract: Low soil fertility has been identified as one of the major causes of decline in yield of cocoa. The importance of fertilizer in ameliorating this problem will go a long way to boost cocoa production. This study therefore assessed the level at which fertilizer is being utilized in cocoa production in Nigeria. The study was carried out between May and June 2008 in five cocoa producing states in Nigeria. These were Ondo, Ekiti, Cross Rivers, Osun and Oyo States. Simple random sampling technique was used to select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 1 publication
6
2
0
1
Order By: Relevance
“…Discussions with farmers on the study plots indicated that cocoa farm fertilization was done in an inconsistent manner over the previous years, depending on access and cost. This falls in line with Appiah et al (1997), who found that cocoa in Ghana is mainly produced by small-scale farmers using few fertilizers, and with Ogunlade et al (2009), who reported that most Nigerian Cocoa farmers do not use fertilizers. Hence, it is no surprise that the baseline soil information (Table 2) shows mixed and low availability of nutrients.…”
Section: Discussionsupporting
confidence: 88%
“…Discussions with farmers on the study plots indicated that cocoa farm fertilization was done in an inconsistent manner over the previous years, depending on access and cost. This falls in line with Appiah et al (1997), who found that cocoa in Ghana is mainly produced by small-scale farmers using few fertilizers, and with Ogunlade et al (2009), who reported that most Nigerian Cocoa farmers do not use fertilizers. Hence, it is no surprise that the baseline soil information (Table 2) shows mixed and low availability of nutrients.…”
Section: Discussionsupporting
confidence: 88%
“…Commercial farmers may be more willing to pay because of the benefit they tend to derive from the services of these private extension agents. This corroborated Ogunlade et al (2009), that there is a strong and positive correlation between farm size, scale of operation and willingness to contribute to sustainable funding. However, 9.4% were not willing to pay.…”
Section: Willingness To Pay and Amount Willing To Pay For Extension Ssupporting
confidence: 69%
“…This can be attributed to soil acidity, causing interference with the availability and uptake of certain nutrients, such as P [27], and the relatively low use of mineral fertilizers [30]. Our results of the farmers interviewed further confirms communications from earlier studies that have consistently shown that most Nigerian cocoa farmers do not use chemical fertilizers [31,4,32,33], hence inadequate nutrients in the soil.…”
Section: Soil Fertility Status Of the Sitessupporting
confidence: 84%